(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
High-rack freezer ware houses present unique fire safety challenges due to extremely low temperatures, high storage density, continuous operation, and limited human occupancy. These conditions can delay fire detection, restrict sprinkler performance, and accelerate fire spread through packaging materials. This project focuses on identifying, analysing, and mitigating fire risks in automated and manually operated high-rack freezer environments. The study evaluates the effectiveness of various fire prevention and suppression strategies, including early-warning detection technologies, inert gas systems, nitrogen-based suppression, thermo graphic monitoring, and optimized warehouse layout design. Industry standards such as NFPA 13, NFPA 72, and cold-storage–specific guidelines are reviewed to assess compliance and performance criteria